KETEPATAN UJI DIAGNOSIS CORONAVIRUS DISEASE 2019 DENGAN METODE REVERSE TRANSCRIPTION LOOP-MEDIATED ISOTHERMAL AMPLIFICATION (RT LAMP): SYSTEMATIC REVIEW - Merry Yustia Karim (2023)
Coronavirus Disease 2019 is a disease that attacks the respiratory tract and is caused by the Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) virus. The tests used to detect COVID-19 cases in Indonesia today are RT PCR and Rapid Antigen Tests. RT-PCR is the gold standard in diagnosing COVID-19, but there are areas for improvement from the technical and economic sides. Another molecular test is reverse transcription loop-mediated isothermal amplification (RT-LAMP). This study aims to determine the diagnostic accuracy of another nucleic acid amplification test, namely RT-LAMP, in diagnosing COVID-19. The design of this study is a systematic review. Literature searches were conducted on four databases, namely Pubmed, Science Direct, Medrxiv and Google Scholar, using the PRISMA-P 2015 method using predetermined keywords. Thirteen studies met the inclusion criteria and were conducted using The Joanna Briggs Institute. The results showed the highest sensitivity value of 98.6% of the nasal and pharyngeal swab sample types, a specificity value of >95% in the entire sample group, the highest positive predictive value of the nasopharyngeal and oropharyngeal swab sampled group of 100% and the highest negative predictive value of 99.9% with the saliva sample type. Sensitivity and specificity are influenced by the magnitude of false negatives and false positives, while the prevalence of the disease influences predictive values. Based on these diagnostic accuracy values, RT-LAMP can be considered an alternative to RT-PCR tests.